2016
DOI: 10.1021/acs.analchem.6b04411
|View full text |Cite
|
Sign up to set email alerts
|

Multicore Magnetic Nanoparticles Coated with Oligomeric Micelles: Characterization and Potential for the Extraction of Contaminants over a Wide Polarity Range

Abstract: Oligomeric micelles from sodium undecylenate (oSUD) were chemisorbed to magnetic iron oxide nanoparticles (MNPs) through a single-step synthetic route involving the simultaneous nanoparticle formation and functionalization in an aqueous medium. The resulting spherical nanoparticles (MNPs-oSUD) consisted of a concatenation of iron oxide cores, with an average size of 7.7 nm, bound by oSUD micelles (particle average diameter of ca. 200 nm). Micellar coverage was ∼50% of the MNP-oSUD (by weight) and offered multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Magnetic nanoparticles are widely used in target extraction and enrichment, because of their outstanding convenience for retrieval from a sample matrix. In addition, the modifiable surface and high specific surface area make it the superior platform for a variety of diverse applications in the field of analytical chemistry. We also noticed the recent reported boronic acid derivatives; ortho -hydroxymethyl-phenylboronic acids (benzoboroxoles) showed excellent water solubility and improved cis -diol units binding capacity, even superior to the Wulff-type boronic acid in neutral water. Inspired by these, we anticipated that the combination of the advantages of magnetic extraction and benzoboroxoles receptor enable the development of a high-efficiency approach for saccharides or glycoproteins detection.…”
mentioning
confidence: 99%
“…Magnetic nanoparticles are widely used in target extraction and enrichment, because of their outstanding convenience for retrieval from a sample matrix. In addition, the modifiable surface and high specific surface area make it the superior platform for a variety of diverse applications in the field of analytical chemistry. We also noticed the recent reported boronic acid derivatives; ortho -hydroxymethyl-phenylboronic acids (benzoboroxoles) showed excellent water solubility and improved cis -diol units binding capacity, even superior to the Wulff-type boronic acid in neutral water. Inspired by these, we anticipated that the combination of the advantages of magnetic extraction and benzoboroxoles receptor enable the development of a high-efficiency approach for saccharides or glycoproteins detection.…”
mentioning
confidence: 99%
“…Over the past decade, magnetic materials have attracted considerable attention due to their excellent performance in the fields of bioassays, drug delivery, electronics, , magnetic resonance imaging, and environmental remediation. As typical magnetic materials, magnetic beads (MBs) can be concentrated, trapped, or used in rapid separation by applying a magnetic field. Owing to their outstanding properties, such as high loading capacity, high magnetic susceptibility, and good biocompatibility, MBs have extensively been used for label-based bioassays such as immunoassays and DNA assays. Particularly, label-based chemiluminescence (CL) technology with MBs has been successfully commercialized in immunoassays.…”
mentioning
confidence: 99%
“…The micelles synthesized in this study showed the good outcomes form the LCST results and anti-inflammation drug releasing tests in a narrow window of pH change of 6.6 and 7.4, which compared other micelles pH-dependent LCST responding to different pH value of 5.5 and 7.4 (Yu et al, 2014) and pH value of 5 and 7.4 (Chen et al, 2013). In addition, magnetic nanoparticle grafted on PNDU micelles provided a higher magnetic property which was 6.67 emu/g, than others MNPs-loaded micelles 0.06 emu/g (Yang et al, 2016), 1.71 emu/g (Naous et al, 2017) it promoted the potential of magnetic targeting or other manipulating application.…”
Section: Discussionmentioning
confidence: 94%